Nutrition Intake as a Risk Factor of Stunting in Children Aged 25–30 Months in Central Jakarta, Indonesia - Ilmani, Dhea Agnia; Fikawati, Sandra (Jurnal Gizi dan Pangan, 2023)
This study aims to determine the relationship between nutrient intake and the incidence of stunting and to determine the dominant factors associated with stunting in children aged 25‒30 months in Gambir and Sawah Besar Districts, Central Jakarta, Indonesia. This research was a quantitative study with a cross-sectional study design. The type of data collected was secondary data from a case control study entitled Differences in Milk Intake and Stunting Incidence in Children Aged 25–30 Months in Central Jakarta in 2019. Data collected included height measurement, questionnaire-based interview, and 24-hour food recall. The percentage of stunting in children aged 25 to 30 months was 29.8%. The factor associated with stunting was iron intake (OR=5.0; 95% CI:1.02–25.25; p<0.05). Stunting was more likely to occur in children with inadequate iron intake than in those with adequate intake. To prevent stunting, iron-rich foods are essential and should be taken in sufficient amounts daily.